PENGARUH KOMPENSASI DAN KARAKTERISTIK EKSEKUTIF TERHADAP AGRESIVITAS PAJAK (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2021) - Cahyati, Tenia Nur; Yuyetta, Etna Nur Afri (Diponegoro Journal of Accounting, 2024)
This study aims to determine and provide empirical evidence regarding the effect of compensation and executive characteristics on tax aggressiveness proxied by effective tax rate. The variables used in this study are executive compensation, foreign directors, directors' accounting expertise, age of the CEO, CEO tenure, and female directors. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019 - 2021. Sampling in this study used purposive sampling method or sampling based on predetermined criteria and total sample was 36 manufacturing companies. This study uses multiple linear regression analysis methods. The results showed that the accounting expertise of directors have a positive and significant effect on tax aggressiveness. The CEO tenure have a negative and significant effect on tax aggressiveness. Meanwhile, executive compensation, foreign directors age of the CEO and female directors have no effect on tax aggressiveness.